Nutrient availability regulates Dendritic cell metabolism and function to modulate T cell responses - Lawless, Simon (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
An emerging view in the field of immunometabolism is that cellular metabolism has a role that extends beyond simply allowing the cell to meet energy and biosynthetic demands, and represents a fundamental physiological mechanism to control immune responses. This is certainly true in CTLs, NK cells and macrophages (Finlay et al., 2012, Donnelly et al., 2014, Tannahill et al., 2013). Work presented in this PhD investigated metabolism in activated BMDCs and how this was related to DC effector function.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin.